Antibacterial activity and metabolite profiling of mangrove endophytic fungus Talaromyces adpressus from Rhizophora apiculata - ANAK AGUNG GEDE INDRANINGRAT; PANDE PUTU CHRISTINE PUTRI PURNAMI; NI MADE AYU SUARDANI SINGAPURWA; MADE DHARMESTI WIJAYA (Society for Indonesian Biodiversity, 2026)
Abstract. Indraningrat AAG, Purnami PPCP, Singapurwa NMAS, Wijaya MD. 2026. Antibacterial activity and metabolite profiling of mangrove endophytic fungus Talaromyces adpressus from Rhizophora apiculata. Biodiversitas 27 (2): d270228. https://doi.org/10.13057/biodiv/d270228. Antimicrobial resistance (AMR) continues to pose a major global health threat and has driven the exploration of under-studied ecosystems, including mangrove forests, as sources of bioactive microorganisms. Therefore, this study aimed to isolate and identify endophytic fungi associated with mangrove roots and to evaluate the antibacterial activity and GC-MS-based metabolite profile of a selected isolate against multidrug-resistant (MDR) bacterial pathogens. The isolate was identified based on morphological characteristics and confirmed by ITS rDNA sequencing, showing 100% similarity to Talaromyces adpressus. Crude ethyl acetate extract obtained from submerged fermentation culture was screened for antibacterial activity against multidrug-resistant (MDR) bacteria, including methicillin-resistant Staphylococcus aureus (MRSA) and extended-spectrum β-lactamase (ESBL)-producing Escherichia coli, Klebsiella pneumoniae, and Acinetobacter baumannii. Agar disc diffusion assays showed measurable inhibition zones of 13.22±1.13 mm (MRSA), 10.41±1.54 mm (ESBL-E. coli), 10.05±1.85 mm (ESBL-A. baumannii), and 9.98±0.11 mm (ESBL-K. pneumoniae). However, broth microdilution assays revealed minimum inhibitory and bactericidal concentrations exceeding 512 µg mL⁻¹ for all tested strains, indicating weak antibacterial potency of the crude extract in liquid culture. GC-MS profiling tentatively identified ten major metabolites, including fatty acids (lauric, myristic, palmitic, oleic acids), diketopiperazines [cyclo(L-Pro-L-Val), cyclo(Phe-Pro)], phenethyl alcohol, phenylacetic acid, 2,4-di-tert-butylphenol, and ergosterol, which have been reported to possess antimicrobial or signaling-modulatory properties. Overall, these findings expand the ecological record of T. adpressus in mangrove ecosystems and provide preliminary antibacterial screening and chemical profiling data, highlighting the need for further fractionation and compound-level validation in future studies. To the best of our knowledge, this is the first report of isolation and characterization of endophytic fungus T. adpressus A1RA from roots of R. apiculata Blume collected from the Ngurah Rai Mangrove Forest, Bali, Indonesia.